Makna Leksikal dan Gramtikal dari Judul Berita Politik Media Online RiauPos.co - Sandi Irawan; Aprillia Maharani Putri; Ira Arini; Pitri Susanti; Muhammad Mukhlis (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2022)
Online newspapers are internet-based newspapers that contain news, articles, and features. The existence of this online news letter is no stranger to the public. This is because online newspapers also play a crucial role in everyday life and become a medium of information. Many people today misunderstand in interpreting the headlines they read. At the same time creating various perspectives in understanding news headlines (headlines). This is often due to ignorance and other factors, including misuse by the author or poor word choice, creating ambiguity among news readers. This study focuses on the lexical and grammatical meaning of political news headlines in the RiauPos.co Online media. This research was conducted in addition to providing an explanation of how news headlines (headlines) can lead to errors, but also trying to convey insights about public perceptions when reading news headlines (headlines). The research entitled "Lexical and Grammatical Meaning of Political News Titles in RiauPos.co Online Media" uses a qualitative approach. This research uses content analysis method. The data source of this research is a collection of political news titles on the RiauPos.co Online media. The data analysis technique in this study uses content analysis. The data collection technique of this research is the documentation technique. Data collection by means of documentation is a method used by researchers to collect data from the RiauPos.co Online media related to political news, especially in a collection of political news titles starting from 17 May 2022 - 06 June 2022. This research is focused on lexical meaning on political news headlines. The results showed that the lexical meaning of political news titles in the RiauPos.co Online media was quite good, it just needed an explanation so that readers could understand it well.